Reposisi Pancasila dari Norm Menjadi Values sebagai Integrasi Pancasila dan Islam - Fatayati, Sun; Mahardika, Ahmad Gelora (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
Pancasila and Islam are two ideologies that are often seen as different. This can be seen from the history of the Indonesian state administration where it is recorded that Pancasila was used as a tool for the Government to dissolve organizations and parties with Islamic nuances, namely Masyumi and HTI. The contradiction was caused by the Government placing Pancasila as part of legal norms, not values. Even though the consequence of placing Pancasila as a legal norm should be that there should also be an agency authorized to conduct trials. However, unlike other legal norms, there is no single institution that has the authority to test Pancasila. In addition, according to experts, Pancasila is a building of values which is the way of life of the Indonesian people. The research method in this article is normative juridical. The result states that Pancasila should be positioned as a value, not as a legal norm.